An Assessment of Sonohysterography as a Diagnostic Tool for Uterine Cavity Defects and Tubal Patency - S Salehpour; R Taheripanah; L Soltani (JRI, 2000)
Introduction: In a prospective blind study, we evaluated sonohysterography (SHG) as a diagnostic tool for uterine cavity and tubal patency and compare SHG with laparoscopy in tubal patency and hysterosalpyngography for Uterine anomaly as gold standard methods. Material and Methods: 76 infertile patients undergone SHG and HSG and laparoscopy and comparison between the different diagnostic techniques for the evaluation of the uterine cavity and tubes was carried out. Results: In comparison between SHG and HSG in the evaluation of uterine cavity, the sensivity of SHG for uterine anomalies was 50% and its specificity was 86.95%. In comparison between SHG and laparoscopy in evaluating tubal patency, specificity of SHG was 81.29% and its sensivity was 28.57% Conclusion: Sonohysterography can be considered as a reliable and accurate method in the first line of evaluation of uterine cavity and tubal patency in infertile patients before HSG, Hysteroscopy, laparoscopy and the all of patients with history of failed IVF.